2004
DOI: 10.3347/kjp.2004.42.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Immunization effect of recombinant P27/30 protein expressed in Escherichia coli against the hard tick Haemaphysalis longicornis (Acari: Ixodidae) in rabbits

Abstract: Abstract:We investigated the induction of resistance to Haemaphysalis longicornis infestation in rabbits that had been immunized with recombinant H. longicornis P27/30 protein. The success of immunological control methods is dependent upon the use of potential key antigens as tick vaccine candidates. Previously, we cloned a gene encoding 27 kDa and 30 kDa proteins (P27/30) of H. longicornis, and identified P27/30 as a troponin I-like protein. In this study, rabbits that were immunized with recombinant P27/30 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The protective mechanism in the host is likely to be at least partially a result of lysis of tick gut epithelial cells through the anti-Ra86 antibodies present in the blood meal taken from vaccinated rabbits, resulting in reduced tick survival and fertility. Such protective mechanisms have also been reported by de la Fuente et al 9 and Almazan et al 33 Similar results were reported by You 40 and Kumar et al, 41 where antibodies were consumed by ticks together with the blood meal and were postulated to damage gut digestive cells, thereby affecting transport of nutrients and tick reproductive performance.…”
Section: Discussionsupporting
confidence: 80%
“…The protective mechanism in the host is likely to be at least partially a result of lysis of tick gut epithelial cells through the anti-Ra86 antibodies present in the blood meal taken from vaccinated rabbits, resulting in reduced tick survival and fertility. Such protective mechanisms have also been reported by de la Fuente et al 9 and Almazan et al 33 Similar results were reported by You 40 and Kumar et al, 41 where antibodies were consumed by ticks together with the blood meal and were postulated to damage gut digestive cells, thereby affecting transport of nutrients and tick reproductive performance.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, tropomyosin has been demonstrated to effectively induce protective responses against other parasites such as the filarial nematode A. viteae as mentioned above. The troponin I-like protein of Haemaphysalis longicornis , which has been considered as a potential vaccine candidate antigen, may be identical to tropomyosin [ 33 ]. Hence, we chose the recombinant protein as a potential candidate antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tick paramyosin in the gut, its potential exposure to ingested host blood and the demonstrated ability to interact with components of the host's immune system has led to the suggestion that it may represent an important new ‘concealed’ antigen for vaccination studies (18). In addition, recombinant versions of the muscle‐associated protein P27/30, a troponin I‐like molecule, have recently been used successfully to produce a protective response in rabbits and mice against infestation with the tick Haemaphysalis longicornis (19,20). Troponin I is a member of a complex containing troponin C which binds Ca 2+ , troponin I which binds actin (thus inhibiting actin–myosin interactions), and troponin T which binds to tropomyosin (21).…”
Section: Research Notementioning
confidence: 99%